A Core Outcome Set for Evaluation of Interventions to Prevent Preterm Birth. Issue 1 (January 2016) - van 't Hooft, Janneke; Duffy, James M. N.; Daly, Mandy; Williamson, Paula R.; Meher, Shireen; Thom, Elizabeth; Saade, George R.; Alfirevic, Zarko; Mol, Ben Willem J.; Khan, Khalid S.
Abstract : OBJECTIVE: To develop a consensus on a set of key clinical outcomes for the evaluation of preventive interventions for preterm birth in asymptomatic pregnant women. METHODS: A two-stage web-based Delphi survey and a face-to-face meeting of key stakeholders were used to develop a consensus on a set of critical and important outcomes. We approached five stakeholder groups (parents, midwives, obstetricians, neonatologists, and researchers) from middle- and high-income countries. Outcomes subjected to the Delphi survey were identified by systematic literature review and stakeholder input. Survey participants scored each outcome on a 9-point Likert scale anchored between 1 (limited importance) and 9 (critical importance). They had the opportunity to reflect on total and stakeholder subgroup feedback between survey stages. For consensus, defined a priori, outcomes required at least 70% of participants of each stakeholder group to score them as "critical" and less than 15% as "limited." RESULTS: A total of 228 participants from five stakeholder groups from three lower middle-income countries, seven upper middle-income countries, and 17 high-income countries were asked to score 31 outcomes. Of these participants, 195 completed the first survey and 174 the second. Consensus was reached on 13 core outcomes: four were related to pregnant women: maternal mortality, maternal infection or inflammation, prelabor rupture of membranes, and harm to mother from intervention. Nine were related to offspring: gestational age at birth, offspring mortality, birth weight, early neurodevelopmental morbidity, late neurodevelopmental morbidity, gastrointestinal morbidity, infection, respiratory morbidity, and harm to offspring from intervention. CONCLUSION: This core outcome set for studies that evaluate prevention of preterm birth developed with an international multidisciplinary perspective will ensure that data from trials that assess prevention of preterm birth can be compared and combined. DATABASE REGISTRATION: COMET Initiative, http://www.comet-initiative.org/studies/details/603, Registration Number: 603. Abstract : A core outcome set for studies that evaluate prevention of preterm birth will ensure that data from trials that assess prevention of preterm birth can be compared and combined.